Editorial: Continuing Islamic Intellectual Tradition - Editor Al-Jami'ah: Journal of Islamic Studies (Al-Jami'ah: Journal of Islamic Studies, 2009)
In a recent discussion forum at Postgraduate Program UIN Sunan Kalijaga Yogyakarta, Greg Barton, an analyst of Indonesian Islamic thought, said that the reason why muslim thinkers in Indonesia are still left behind in promoting their ideas globally is because of a lack of their works being found in English. No one doubts that Islamic discourse in Indonesia is very dynamic and shows constant development. We have, for example, neo-modernist muslim thinkers such as Nurcholish Madjid, Abdurrahman Wahid, Djohan Efendy, and Ahmad Wahib. There are muslim intellectual reformers such as Harun Nasution, Mukti Ali, Munawir Sjadzali, Amin Abdullah, Syafi’i Ma’arif, and Abdul Munir Mulkhan. There are also progressive muslim thinkers such Masdar Farid Mas’ud, Mansour Fakih, and Muslim Abdurrahman, to name a few. We can list still more Indonesian muslim intellectuals. However, one important question must be asked: how many of these  thinkers produce their works in English so that their thought can reach  a wider intellectual audience, not only in Indonesia but outside as well?